2017
DOI: 10.1515/cerce-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytotoxicity of Aqueous Extracts of Centaurea maculosa and Melilotus officinalis on Germinability and Growth of Wheat

Abstract: ABSTRACT. Weed incursion in cultivated fields is a serious biological problem, which causes considerable yield losses of economically important field crops through allelopathy and competitive interactions. Spotted knapweed (Centaurea maculosa) and yellow melilot (Melilotus officinalis) are among the most prevalent weeds in cultivated fields of Pakistan, particularly in wheat fields. Like many other weeds, they may pose allelopathic and competitive challenges to field crops. The objective of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For example, Phragmites australis suppresses the growth of other species plants in surroundings by releasing a phytotoxin compound (Rudrappa et al 2009). Recently, researchers have track down the release of allelochemicals in some invasive plants, like Centauera stoebe (Gfeller et al 2019), Canada goldenrod (Wang et al 2018), C. stoebe, and Melilotus officinalis (Siyar et al 2017), that may inhabit native plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Phragmites australis suppresses the growth of other species plants in surroundings by releasing a phytotoxin compound (Rudrappa et al 2009). Recently, researchers have track down the release of allelochemicals in some invasive plants, like Centauera stoebe (Gfeller et al 2019), Canada goldenrod (Wang et al 2018), C. stoebe, and Melilotus officinalis (Siyar et al 2017), that may inhabit native plants.…”
Section: Introductionmentioning
confidence: 99%
“…It is used as food for human consumption as well as food grain for animals (Moussa, 2001). Siyar et al (2017) reported that weed incursion in cultivated fields is a serious biological problem, which causes considerable yield losses of economically important field crops through allelopathy and competitive interactions. Allelopathic interactions are mediated by secondary metabolites (allelochemicals) released through leaching, root exudation, volatilization and residue decomposition into the environment and affect growth and development in natural environments and agro-ecosystems (Cheema et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, agroforestry trees release allelochemicals to rhizosphere, which may establish negative or stimulatory allelopathic interactions with cultivated crops, weeds and microorganisms. Although, all parts of the agroforestry trees may exhibit allelopathy; however, leaves and roots are primary organs, which have strong potential for allelopathic interactions (Narwal, 2000;Majeed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%